CISTO DENTÍGERO - Agnol, Wesley Dall; Gonçalves, Andressa; Petroli, Larissa; Fantinelli, Tainara; Werlang, Fábio André; Tomazelli, Karin Berria (Anais de Odontologia / ISSN 2526-9437; v. 3 n. 1 (2018): 2018/1, 2018)
.